Utilizing Cow Dung Manage Into Crafts And Paper Canvas To Draw - Aufa, Raihan Syihab; Supriyatna, Ateng; Argiansyah, Muhamad Ilham; Zakaria, Dadang (Edumaspul: Jurnal Pendidikan, 2023)
Cow dung, as an abundant organic waste in the livestock sector, has gained attention as an alternative raw material source for the paper industry. This study aims to explore the potential and environmental benefits of utilizing cow dung in paper production. This study uses a qualitative descriptive method in which the author describes phenomenon and situation deep down. The study utilizes a scientific and technological approach with experimental analysis methods to identify the composition of cow dung and evaluate its potential as a raw material in the paper industry. Findings from this research reveal that cow dung contains a significant amount of coarse fibers and organic matter, which can be utilized as a primary component in paper manufacturing. The coarse fibers present in cow dung can be processed into pulp through appropriate chemical or mechanical treatments. Apart from serving as a fiber source, the utilization of cow dung in the paper industry has positive environmental impacts. The use of cow dung as a raw material for paper production can reduce the amount of waste disposed into the environment, thereby helping to mitigate soil and water pollution. Additionally, this approach can also reduce the paper industry’s reliance on limited natural resources, such as wood.